Asuhan Keperawatan Pada Tn. S dengan Harga Diri Rendah di Ruang Maespati Rumah Sakit Jiwa Daerah Surakarta - Mulyono, Andri, Sahuri Teguh, S.Kep., Ns (2013)
Low self-esteem is a feeling of shame or inferiority because of the flaws in ourselves that is usually by a negative assessment of themselves or others in the same neighborhood. To determine nursing care to patients with mental disorders with low self-esteem include assessment, intervention, implementation, and evaluation of nursing. After 3 days of nursing care, the obtained results are the client can understand and can repeat back from what has been discussed together. But has not achieved all of the evaluation criteria and not in accordance with nursing interventions, in because of the family has not had time to visit clients and actively participate in helping clients in addressing issues of self-esteem. Cooperation between the healthcare team and the patient along with the patient's family are essential for the success of nursing care to patients, therapeutic communication can encourage more cooperative patient.